2006
DOI: 10.1038/sj.bmt.1705257
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for treatment-related mortality after bone marrow transplantation in GSTM1-positive recipients

Abstract: Treatment-related mortality (TRM) is a major obstacle to successful allogeneic hematopoietic stem cell transplantation (HSCT). A variety of drugs are used in allogeneic HSCT, and a genetic polymorphism in metabolic enzymes could affect the metabolism of drugs and potentially influence TRM. Here, we focused attention on GSTM1 and GSTT1 enzymes, which metabolize chemotherapeutic agents, chemical carcinogens and by-products of oxidative stress and are absent from more than 50% of some populations. To assess the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…The second androgen-conjugating enzymes expressed in the prostate, UGT2B17, have also attracted attention. Interestingly, the complete deletion of the human UGT2B17 gene has been reported in humans, and this polymorphism is associated to a risk factor for high transplant related mortality because the UGT2B17 enzyme can be immunogenic in the recipient with homozygous UGT2B17 deletion [61,62]. Wilson et al, reported that DNA spanning the UGT2B17 gene is absent in 9 of the 40 DNA human samples examined and that the allele frequency varies between the two ethnic groups African Americans (allele frequency 0.21) and Caucasians (allele frequency 0.33) [63].…”
Section: Polymorphism In Ugt2b15 Gene and Deletion Of Ugt2b17 Genementioning
confidence: 98%
“…The second androgen-conjugating enzymes expressed in the prostate, UGT2B17, have also attracted attention. Interestingly, the complete deletion of the human UGT2B17 gene has been reported in humans, and this polymorphism is associated to a risk factor for high transplant related mortality because the UGT2B17 enzyme can be immunogenic in the recipient with homozygous UGT2B17 deletion [61,62]. Wilson et al, reported that DNA spanning the UGT2B17 gene is absent in 9 of the 40 DNA human samples examined and that the allele frequency varies between the two ethnic groups African Americans (allele frequency 0.21) and Caucasians (allele frequency 0.33) [63].…”
Section: Polymorphism In Ugt2b15 Gene and Deletion Of Ugt2b17 Genementioning
confidence: 98%
“…Non-HLA genetic polymorphisms that can predict the risk and severity of GVHD are found in genes encoding minor histocompatibility antigens, pro-and anti-inflammatory cytokines, non-cytokine immunoregulators, and drug-metabolizing enzymes [4][5][6][7]. In a previous study, we analyzed the association between homozygous glutathione S-transferase M1 and T1 gene deletions in the recipient and donor with various outcomes of HSCT, and we found a significant association between the presence of the glutathione S-transferase M1 enzyme in the recipients and higher treatment-related mortality (TRM) as well as a lower rate of survival [8]. In another study, we reported that a homozygous gene deletion leading to a null phenotype for the UDP-glycosyltransferase 2 family, polypeptide B17 enzyme [9], is an independent risk factor for higher TRM and lower survival after HSCT [10].…”
Section: Introductionmentioning
confidence: 91%
“…The same group reported similar findings when they investigated 2 additional genes, GSTM1 and GSTT1, in 373 HLA-matched unrelated HSCT pairs. 43 GSTM1 and GSTT1 were also identified as homozygous null at appreciable frequency in the Hapmap population. 9 GSTT1 has been identified as a potential alloantigen mediating de novo immune hepatitis in liver transplant recipients who are homozygous null for the gene, but receive a GSTT1 ϩ graft.…”
Section: Minor Histocompatibility Antigensmentioning
confidence: 99%